Interstellar comet 2I/Borisov exhibits a structure similar to native Solar system comets. (18th April 2020) - Manzini, F; Oldani, V; Ochner, P; Bedin, L R
ABSTRACT: We processed images taken with the Hubble Space Telescope ( HST ) to investigate any morphological features in the inner coma suggestive of a peculiar activity on the nucleus of the interstellar comet 2I/Borisov. The coma shows an evident elongation, in the position angle (PA) ∼0−180 ○ direction, which appears related to the presence of a jet originating from a single active source on the nucleus. A counterpart of this jet directed towards PA ∼10 ○ was detected through analysis of the changes of the inner coma morphology on HST images taken on different dates and processed with different filters. These findings indicate that the nucleus is probably rotating with a spin axis projected near the plane of the sky and oriented at PA ∼100−280 ○ , and that the active source is lying in a near-equatorial position. Subsequent observations of HST allowed us to determine the direction of the spin axis at right ascension (RA) = 17 h 20 m ± 15 ○ and declination (Dec.) = $-35^° \, ± 10^°$ . Photometry of the nucleus on HST images of 2019 October 12 only spans ∼7 h, insufficient to reveal a rotational period. The morphology exhibited by the interstellar comet 2I/Borisov is very similar to that of comet C/2014 B1 suggesting that the activation processes are the same as those observed in the Solar system native comets.